Characterization of Active Integrated Multicore Waveguides - Benedicto, David; Martín, Juan Carlos; Vallés, Juan Antonio (Jornada de Jóvenes Investigadores del I3A, 2018)
This study includes the experimental both passive and active characterization of multicore waveguides written in phosphate glass codoped with erbium and ytterbium, with the aim of designing and optimizing photonic devices based on this type of structures.